The Religiusity Of The Wali Topeng Sidhakarya In The Religious Life Of Hindus In Bali - I Wayan Eka (International Journal of Multidisciplinary Sciences, 2023)
In the era of modernization that is happening in the life of the Balinese people today, mask dance still has a position as a work of art that has high value. Cultural arts in Bali are commonly used as a complement to the implementation of upācāra yajña. Based on the decision of the sacred arts seminar, the types of dances in Bali are as follows: Wali Dance (Religious Dance), Bebali Dance (Ceremonial Dance), Balih-balihan Dance (Secular Dance). In particular, this article will discuss the Bebali Dance Art (Ceremonial Dance), namely the Wali Topeng Sidhakarya. In several discussion articles that were used as specific references, there was no discussion related to the religiosity of the Wali Topeng Sidhakarya. For this reason, the main issues raised in this article are: (1) how is the mythology of Dalem Sidhakarya in Bali? (2) the religiosity value of Wali Topeng Sidhakarya in the religious life of Hindus in Bali. The method used is descriptive qualitative with an art transformation approach. Data collection techniques through observation on documents or sources that are relevant to the object of research. Data analysis is inductive/qualitative, the results of the research describe the interpretation of meaning based on the phenomena encountered. The conclusion from the results of this study shows that historiographically the Wali Topeng Sidhakarya in the implementation of the upācāra yajña in Bali has a very important role because the upācāra yajña is believed to be imperfect if it has not presented the Wali Topeng Sidhakarya. Wali Topeng Sidhakarya carries out three main concepts namely Satyam (truth), Śiwam (holiness) and Sundaram (harmony). The religiosity inherent in the Wali Topeng Sidhakarya sasolahan includes six dimensions, namely the dimensions of belief (theology), religious practice (ritualistic), practice, appreciation, and knowledge which as a whole contribute to the inculcation of Hindu spiritual values.